2015
DOI: 10.1128/jvi.02383-14
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3A Functions as a Restriction Factor of Human Papillomavirus

Abstract: Human papillomaviruses (HPVs) are small DNA viruses causally associated with benign warts and multiple cancers, including cervical and head-and-neck cancers. While the vast majority of people are exposed to HPV, most instances of infection are cleared naturally. However, the intrinsic host defense mechanisms that block the early establishment of HPV infections remain mysterious. Several antiviral cytidine deaminases of the human APOBEC3 (hA3) family have been identified as potent viral DNA mutators. While edit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
203
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(219 citation statements)
references
References 77 publications
7
203
2
3
Order By: Relevance
“…The preponderance of A3 mutations in HPV driven cervical cancer, together with the observation that A3 mutations are enriched in the HPVassociated subset of head and neck squamous cell carcinoma (HNSC), suggest a possible off-target response to the virus [37,38,43,44]. Consistent with this, HPV16 infection has recently been shown to upregulate A3A and A3B mRNA expression in a keratinocyte cell line, and both are upregulated in pre-invasive cervical lesions [19,45]. However, within cervical cancer and HNSC the enrichment of A3 signature mutations is not related to the expression of A3 genes, at least as seen in the tumor biopsy [43,44].…”
Section: A3 Expression and Stimulationmentioning
confidence: 80%
See 1 more Smart Citation
“…The preponderance of A3 mutations in HPV driven cervical cancer, together with the observation that A3 mutations are enriched in the HPVassociated subset of head and neck squamous cell carcinoma (HNSC), suggest a possible off-target response to the virus [37,38,43,44]. Consistent with this, HPV16 infection has recently been shown to upregulate A3A and A3B mRNA expression in a keratinocyte cell line, and both are upregulated in pre-invasive cervical lesions [19,45]. However, within cervical cancer and HNSC the enrichment of A3 signature mutations is not related to the expression of A3 genes, at least as seen in the tumor biopsy [43,44].…”
Section: A3 Expression and Stimulationmentioning
confidence: 80%
“…While A3G resides in the cytoplasm, where it becomes incorporated into retroviral virions, A3 enzymes such as A3A, A3B and A3C enter the nucleus, where they are able to target other pathogens including human papillomaviruses (HPV) and also retrotransposons; mobile elements within the genome which appear to be targeted by multiple APOBEC enzymes via a variety of mechanisms [12][13][14][15][16][17][18][19]. With nuclear localization however, comes the risk of off-target activity against host genomic DNA and the potential for mutagenesis.…”
Section: Deoxycytidine Deamination In Innate Immunity and Somatic Mutmentioning
confidence: 99%
“…comparison to levels in normal tissues, and this upregulation is possibly due to HPV16 oncoproteins E6/ E7 (31). A previous study noted the expression of three genes of the APOBEC3A family, hA3A, hA3B, and hA3H, in skin keratinocytes, which are the main host cells for HPV infection (32).…”
Section: Effects Of Hpv Viral Infection On Apobec Expressionmentioning
confidence: 99%
“…A3A is among the most potent of the human APOBEC3 deaminases, and can restrict nuclear DNA viruses and retrotransposition events. 8,[34][35][36] We recently showed that the mechanism for A3A inhibition of L1 retrotransposition occurs by deamination of ssDNA transiently exposed during L1 integration. 9 We have also previously shown that A3A can act on the cellular genome to induce DNA breaks that activate the DNA damage response (DDR).…”
Section: Introductionmentioning
confidence: 99%